Training in service: perception of health workers in assistance in federal prison units - Lana Jocasta de Souza Brito; Silvia Helena Henriques; Cléria Bragança; Laura Andrian Leal (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objectives: To characterize the in-service training process of health workers from federal prison units. Method: This is a qualitative descriptive-exploratory study. The information was collected through semi-structured interviews with professionals of the referred services, from June to October 2018. Results: Data analysis revealed that health professionals were unaware of the work performed within these establishments and that the concern of these institutions by the improvement of these workers is recent and marked by isolated actions. Of the courses offered, few contemplate the reality of prison health causing the server to seek knowledge on their own. Due to the violent and confining environment, the health team lacks courses such as defense and weaponry. Conclusions and implications for practice: The study reveals flaws in the training strategies offered by the organization and incipient managerial awareness about the professional and emotional preparation of these workers.